APLIKASI PROGRAM LINIER INTEGER 0-1 UNTUK MENYUSUN JADWAL USULAN PIKET SATPOL PP - Hermanto, Koko; Suarantalla, Ryan; Sahdan, Sahdan (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2020)
A zero-one integer linear programming with the Lindo software approach can be used to solve the cyclical scheduler method problem. The cyclical scheduling method is one of the scheduling methods that can be used to schedule work picks from Satuan Polisi Pamong Praja (Satpol PP), where each Satpol PP will work within a specified period of 5 days and will repeat periodically. The decision variable solution to the linear programming model is zero or one which becomes the decision of the Satpol PP in choosing the type of schedule. The preparation of this proposed schedule pays attention to the preferred weight of the Satpol PP holidays in each type of schedule that is formed so that the objective function of the linear programming model is to maximize the preferred holiday weights per Satpol PP against the existing schedule types. The results of the analysis obtained an optimal proposal schedule in maximizing the quality of assignments to each shift while taking into account the workload and constraints that exist. Also, it is known comparison between proposal scheduling and scheduling that has been used so far is seen in the aspect of quality, and fairness of the schedule carried out in the proposed scheduling is superior.